Effect of microbial load on the condition index of the edible oyster, Saccostrea cucullata in the Sundarbans, India - Jana, Harekrishna; Mondal, Keshab Chandra; Maity, Chiranjit; Das, Arpan; Halder, Suman Kumar; Mitra, Abhijit; Pati, Bikas Ranjan (International journal of aquatic biology, 2014)
;The effect of microbial load on the condition Index of the edible oyster, Saccostrea cucullata were analysed on monthly basis during 2010 and 2011 from the three different stations (Namkhana, Frasergaunge and Sajnekhali) of Indian Sundarbans. The results showed significant variation with respect to microbial load between stations and seasons, which is reflected in the tissue of edible oyster. Significant positive correlations were observed between microbial load of the ambient environment and the tissue system of oyster. The Condition Index of the oyster species also exhibited negative correlation with the microbial load of oyster tissue, which confirms the negative stress induced by microbes on the growth and survival of the species.